Pendampingan dan Pembinaan Pedagang Asongan Sekolah dalam Menghilangkan Bahan Berbahaya di SD Wilayah Kabupaten Sleman: Indonesia - Sunarto, Sunarto; Agustiningtyas, Irena; Jeem, Yaltafit Abror (Jurnal Abdimas Madani dan Lestari (JAMALI), 2025)
Fulfillment of quality and safe food is the human right of every Indonesian citizen. However, research results show that many cases of disease in the community occur due to food poisoning, and in fact most often occur in children. Meanwhile, there is a government program called the national movement towards school children's snacks (PJAS) that are safe, healthy and clean. The facts show that many hawkers do not understand the importance of this movement in applying it to their merchandise. The aim of this service activity is to provide guidance, training, mentoring and inspection of food additives and microbes in the snacks of hawkers in the Sleman Regency area, especially for members of the Mugo Lestari School Hawker Community (KUPAS), especially in one of the elementary schools in Sleman. The methods used in this activity are guidance, training and assistance to hawkers. Various outreach activities, coaching the KUPAS organization and several times providing subsidies to carry out laboratory tests on school snacks produced by KUPAS members. One of the qualitative results of checking school snacks, there were still several member products that detected E Coli, rhodamine, borax, formalin. Efforts to follow up this activity by giving stickers to traders for those who meet the safe criteria for laboratory examination. Laboratory test results that still contain contaminated materials are carried out by coaching and food testing until the total is negative.